The Balloon-borne Large-Aperture Submillimeter Telescope for polarization: BLAST-pol - Marsden, G.; Ade, P.A.R.; Benton, S.; Bock, J. J.; Chapin, E. L.; Chung, J.; Devlin, M. J.; Dicker, S.; Fissel, L.; Griffin, M.; Gundersen, J. O.; Halpern, M.; et al. (SPIE Proceedings, Millimeter and Submillimeter Detectors and Instrumentation for Astronomy IV, 2008)
International audience The Balloon-borne Large Aperture Submillimeter Telescope (BLAST) is a sub-orbital experiment designed to study the process of star formation in local galaxies (including the Milky Way) and in galaxies at cosmological distances. Using a 2m Cassegrain telescope, BLAST images the sky onto a focal plane, which consists of 270 bolometric detectors split between three arrays, observing simultaneously in 30% wide bands, centered at 250, 350, and 500 ?m. The diffraction-limited optical system provides a resolution of 30" at 250 ?m. The pointing system enables raster-like scans with a positional accuracy of ~30", reconstructed to better than 5" rms in postflight analysis. BLAST had two successful flights, from the Arctic in 2005, and from Antarctica in 2006, which provided the first high-resolution and large-area (~0.8-200 deg2) submillimeter surveys at these wavelengths. As a pathfinder for the SPIRE instrument on Herschel, BLAST shares with the ESA satellite similar focal plane technology and scientific motivation. A third flight in 2009 will see the instrument modified to be polarization-sensitive (BLAST-pol). With its unprecedented mapping speed and resolution, BLAST-pol will provide insights into Galactic star-forming nurseries, and give the necessary link between the larger, coarse resolution surveys and the narrow, resolved observations of star-forming structures from space and ground based instruments being commissioned in the next 5 years.